Active fractions of golden-flowered tea (Camellia nitidissima Chi) inhibit epidermal growth factor receptor mutated non-small cell lung cancer via multiple pathways and targets in vitro and in vivo - Wang, Ziling; Hou, Xiaoying; Li, Min; Ji, Rongsheng; Li, Zhouyuan; Wang, Yuqiao; Guo, Yujie; Liu, Dahui; Huang, Bisheng; Du, Hongzhi (Frontiers in Nutrition, 2022)
As a medicine-food homology (MFH) plant, golden-flowered tea (Camellia nitidissima Chi, CNC) has many different pharmacologic activities and is known as “the queen of the tea family” and “the Panda of the Plant world”. Several studies have revealed the pharmacologic effects of CNC crude extract, including anti-tumor, anti-oxidative and hepatoprotective activity. However, there are few studies on the anti-tumor active fractions and components of CNC, yet the underlying mechanism has not been investigated. Thus, we sought to verify the anti-non-small cell lung cancer (NSCLC) effects of four active fractions of CNC. Firstly, we determined the pharmacodynamic material basis of the four active fractions of CNC (Camellia. leave. saponins, Camellia. leave. polyphenols, Camellia. flower. saponins, Camellia. flower. polyphenols) by UPLC-Q-TOF-MS/MS and confirmed the differences in their specific compound contents. Then, MTT, colony formation assay and EdU incorporation assay confirmed that all fractions of CNC exhibit significant inhibitory on NSCLC, especially the Camellia. leave. saponins (CLS) fraction on EGFR mutated NSCLC cell lines. Moreover, transcriptome analysis revealed that the inhibition of NSCLC cell growth by CLS may be via three pathways, including “Cytokine-cytokine receptor interaction,” “PI3K-Akt signaling pathway” and “MAPK signaling pathway.” Subsequently, quantitative real-time PCR (RT-qPCR) and Western blot (WB) revealed TGFB2, INHBB, PIK3R3, ITGB8, TrkB and CACNA1D as the critical targets for the anti-tumor effects of CLS in vitro. Finally, the xenograft models confirmed that CLS treatment effectively suppressed tumor growth, and the key targets were also verified in vivo. These observations suggest that golden-flowered tea could be developed as a functional tea drink with anti-cancer ability, providing an essential molecular mechanism foundation for MFH medicine treating NSCLC.